Pengaruh Penerapan Kinerja Lingkungan Terhadap Return Saham (Studi Kasus pada Perusahaan-Perusahaan di Negara Berkembang Wilayah ASEAN yang Terdaftar di Bloomberg Periode 2014 – 2022) - Gunawan, Devi Nathania; Anggraini, Melisa (Applied Research in Management and Business, 2024)
Companies must consider environmental performance in the current global economic era in order to compete with other competitors. Environmental performance will provide signals for investors in their investment decisions that will affect the stock returns of related companies. The purpose of this study is to examine the influence of environmental performance on stock returns. The research method used is a quantitative research method using a paired sample t-test to see if there is a difference in stock returns when companies announce their environmental performance scores. The results of the study show that there is a difference in stock returns when companies announce their environmental performance scores.